Improved Techniques For Power Consumption Reduction In Portable Two-Way Radio - Adrian, Lim Hooi Jin (2013)
In the two-way portable radios market, long battery life has become an essential and critical customer requirement for communication during critical public safety or rescue missions. Thus, in tandem with this need, various researches have been conducted by industry players to reduce the power consumption of the design with minimum sacrifices on product performance. This thesis presents various key techniques that can be adopted into the design of portable two ways radio to reduce the overall power consumptions of radio in three main areas in the portable radio architecture from system level perspective; DC power supply topology for CMOS based processor, LCD and keypad backlighting system and RF sections at idle mode. In the DC power supply topology for CMOS based processor area, two techniques were identified to optimize the overall efficiency of the power distribution network by minimizing the power conversion lost in the multiple power conversion line up and utilization of single and direct conversion in the portable radio architecture to save up to 58% of power at battery input and prolonging the battery life of the portable two-way radio by another 2.23 hours. Meanwhile, in the LCD and keypad backlighting system, three techniques are identified to reduce the power consumptions at battery input of up to 24% which includes careful selection of LED, light guide and power management topology to drive the LEDs in an efficient manner and prolonging the battery life of the portable two-way radio by another 0.39 hours.